METAVERSE IN EDUCATION – TEACHERS’ PERSPECTIVES ON BENEFITS AND CHALLENGES - Sofija Matović; Tamara Marković; Nikoleta Dobrosavljević; Miljana Stajin (Istraživanja u Pedagogiji)
The metaverse, powered by artificial intelligence and integrating virtual, augmented, and mixed reality, represents an emerging technology with the potential to transform education by creating immersive learning environments. As confirmed by previous research worldwide, teachers at different educational levels recognize its possibilities in education. Alongside numerous benefits, concerns exist that the implementation of the metaverse could lead to certain negative consequences, some of which relate to teachers' insufficient competence for its purposeful use in teaching. For this reason, there is a need to investigate the attitudes of Serbian teachers regarding this concept. This study aimed to examine the attitudes of 108 pre service and in-service primary school teachers toward the role of the metaverse in education, with a particular focus on the use of a metaverse-based educational platform model. The collected data were analyzed using descriptive statistics. The results suggest that respondents generally view the metaverse in education positively, valuing its role in exploring abstract and distant content and enhancing teaching efficiency. However, material-technical limitations pose a significant challenge, alongside concerns about the potential dehumanization of education. Teachers' resistance to new teaching models is partly rooted in insufficient training for artificial intelligence-based concepts applications in education. The results highlight the need for systematic professional development, advocating for its integration into initial teacher education curricula to ensure the effective and pedagogically purposeful use of technology.